PEMBENTUKAN KARAKTER DISIPLIN DAN PERILAKU SISWA MELALUI KEGIATAN PEMBIASAAN PAGI DI SMP NEGERI 2 SAWIT (Universitas Merdeka Madiun, 2025)
Globalization has many impacts on everyone's life. Naturally, this has both positive and negative effects, more adverse consequences in the event that we don't respond carefully. Discipline and character play a crucial role in life. With the formation of a strong disciplined character, good human character is also created. Observations of junior high school students have revealed a number of extremely troubling character issues. This character weakness is most common among adolescents in their junior year of high school, when they are more likely to absorb negative influences from their developmental age. The purpose of this study is to determine how morning habituation activities at SMP Negeri 2 Sawit can shape students' attitudes toward discipline and behavior. This research uses a descriptive qualitative method. The data collection process was carried out by interviews and direct observation of teachers and students at SMPN 2 Sawit. The results showed that from the process carried out in the formation of disciplinary character through habituation activities there was an increase in disciplinary character in students.